Digital Forensics and Humans: Insights from Jurnal Articles - Oktavia, Herlina; Multazam, Mochammad Tanzil; Hasan, Rizqi (Proceedings of The ICECRS, 2023)
This data article presents the results of a search for jurnal articles related to digital forensics and humans using the keyword "digital forensic AND humans" on lens.org. The data was filtered by document type, data range, and subject matter, resulting in 625 jurnal articles published between 2012 and 2022 in the field of law. The data provides insights into the top institutions, fields of study, authors, and publishers in the field of digital forensics. The article highlights the importance of data collection and preservation in digital forensics, the complexity of data, and the need for appropriate legal standards in the data acquisition process. The data is useful for researchers and professionals in the field of digital forensics and cybersecurity.Highlights: The importance of data collection and preservation in digital forensics The complexity of data in digital forensics The need for appropriate legal standards in the data acquisition process Keywords: digital forensics, humans, data collection, data acquisition, cybersecurity